2021
DOI: 10.1097/corr.0000000000001727
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Facial Expression of Emotion Corresponds with Patient Mindset

Abstract: Background Mental health has a notable and perhaps underappreciated relationship with symptom intensity related to musculoskeletal pathophysiology. Tools for increasing awareness of mental health opportunities may help musculoskeletal specialists identify and address psychological distress and unhealthy misconceptions with greater confidence. One such type of technology—software that identifies emotions by analyzing facial expressions—could be developed as a clinician-awareness tool. A first step i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…A study exploring the effects of communication skills training on care associated with patient emotional distress in the primary care setting randomized communication skills–trained clinicians and nontrained clinicians and found that trained clinicians reported more psychosocial problems, engaged in more strategies to manage emotional problems, and scored higher in clinical proficiency; additionally, their patients reported reductions in emotional distress up to 6 months after the clinical visit [62]. Although the current evidence reveals limited relationships between mindset and patient experience [7, 77], the high ceiling effect of patient-reported experience measures might hinder the ability to identify correlations with perception of clinician empathy [17, 49, 78].…”
Section: Discussionmentioning
confidence: 99%
“…A study exploring the effects of communication skills training on care associated with patient emotional distress in the primary care setting randomized communication skills–trained clinicians and nontrained clinicians and found that trained clinicians reported more psychosocial problems, engaged in more strategies to manage emotional problems, and scored higher in clinical proficiency; additionally, their patients reported reductions in emotional distress up to 6 months after the clinical visit [62]. Although the current evidence reveals limited relationships between mindset and patient experience [7, 77], the high ceiling effect of patient-reported experience measures might hinder the ability to identify correlations with perception of clinician empathy [17, 49, 78].…”
Section: Discussionmentioning
confidence: 99%
“…Experienced doctors will usually identify unhelpful thoughts and symptoms of distress. Indeed, there is evidence that clinician facial expression of emotions correlates with the patient’s mindset, even if this is sometimes subconscious (Versluijs et al., 2021). The patient’s language in a consultation can signal unhelpful thoughts, including phrases such as ‘I can’t’ and ‘Something is wrong’, which are associated with unhelpful thinking (Bot et al., 2012).…”
Section: Ways In Which Mental Health Manifests In Upper Limb Speciali...mentioning
confidence: 99%
“…For instance, current measures may not adequately assess nonverbal communication such as facial expressions [19,33], body language [35], and the linguistic and paralinguistic vocal cues in speech [17]. A study that documented correspondence between computer-rated emotional content of clinician facial expressions and patient thoughts and feelings regarding symptoms suggests computer-based tools can help identify aspects of patient-clinician interaction to improve patient experience [33]. Another study documented that natural language processing of verbatim text comments from patients about their care experience resulted in a more normal distribution of patient experience scores and no ceiling effect [27].…”
Section: Association Between Clinician Communication Effectiveness An...mentioning
confidence: 99%
“…We may benefit from better ways for independent observers to discern the key elements of a patient-clinician interaction. For instance, current measures may not adequately assess nonverbal communication such as facial expressions [19,33], body language [35], and the linguistic and paralinguistic vocal cues in speech [17]. A study that documented correspondence between computer-rated emotional content of clinician facial expressions and patient thoughts and feelings regarding symptoms suggests computer-based tools can help identify aspects of patient-clinician interaction to improve patient experience [33].…”
Section: Association Between Clinician Communication Effectiveness An...mentioning
confidence: 99%